Effectiveness of Applying the Theory of Planned Behavior with Yoga Program on the Physical Activity and Mental Health of the Prefrailty Older Adults - Ya Ting Wu; Miao Yen Chen; Yung Cheng Huang; Chieh Yu Liu (International Journal of Yoga)
Objectives: Grounded in the theory of planned behavior (TPB), this study evaluated the effectiveness of a yoga program intervention on the physical functioning and mental health in older adults. Materials and Methods: This was a quasi-experimental two-group, pre- and posttest, single-blind study. The participants were older adults above 65 years of age and in the early stage of frailty. The intervention for the experimental group was a twice weekly 60-min yoga session for 12 weeks; the control group received physical activity lectures in the 1st and 8th weeks. Pretest is conducted before the intervention, posttest one is conducted in the 8th week, and posttest two is conducted in the 12th week. Outcome indicators include physical activity level, body balance, flexibility, lower limb muscle strength, mental health (Brief Symptom Rating Scale [BSRS]), exercise behavior questionnaire, etc., Results: After 12-week silver yoga intervention, there were 31 participants in the experimental group with a loss of 9% (29% loss rate), whereas there were 29 participants in the control group with a loss of 6% (20% loss rate). Results from generalized estimating equations that grip strength index (P = 0.000), right lower limb muscle strength (P = 0.000), left lower limb muscle strength (P = 0.000) were significant between groups for both experimental and control groups, whereas other outcome indicators such as physical activity level, balance, flexibility, and mental health were not significant between groups. However, experimental within-group mean differences at week 12 for grip strength (P = 0.000), BSRS (P = 0.016), physical activity level (P = 0.000), right lower limb muscle strength (P = 0.000), left lower limb muscle strength (P = 0.000), simple physical function assessment (P = 0.000), single-leg standing (P = 0.000), upper limb flexibility (P = 0.000), lower limb flexibility (P = 0.000), exercise behavior evaluation attitude (P = 0.000), and exercise behavior evaluation perceived behavioral control (P = 0.000) were all significant. Conclusions: This study uses Ajzen’s TPB as a basis to explore the behavioral intention after silver yoga intervention. This theory believes that an individual’s specific behavior is affected by his or her behavioral intention, and the behavioral intention depends on the actor’s attitude and subjective attitude toward the behavior. Norms perceived behavioral control. The research results show that yoga intervention attitude has the highest impact on behavioral intention, followed by perceived behavioral control and finally subjective norms. The experimental group has changed their attitudes and cognitions to increase their behavioral intentions. They have a deeper understanding of yoga asanas. They have broken through the difficult limb bending and kneeling postures seen in the past, which has increased their participation in yoga activities and confidence in their perceived behaviors. It also enhances behavioral intention, which means that the attitude and personal behavior of the research subjects after the intervention increase the elder’s exercise intention, making the elder more clearly aware that yoga asanas are competent, thereby increasing the regularity of activity participation.